Synthesis of 2,1,3-Benzoxadiazole Derivatives as New Fluorophores—Combined Experimental, Optical, Electro, and Theoretical Study - Frizon, Tiago E. A.; Vieira, André A.; da Silva, Fabricia N.; Saba, Sumbal; Farias, Giliandro; de Souza, Bernardo; Zapp, Eduardo; Lôpo, Michell N.; Braga, Hugo de C.; Grillo, Felipe; Curcio, Sergio F.; Cazati, Thiago; et al. (Frontiers in Chemistry, 2020)
Herein, we report the synthesis and characterization of fluorophores containing a 2,1,3-benzoxadiazole unit associated with a π-conjugated system (D-π-A-π-D). These new fluorophores in solution exhibited an absorption maximum at around ~419 nm (visible region), as expected for electronic transitions of the π-π* type (ε ~ 2.7 ×107 L mol-1 cm-1), and strong solvent-dependent fluorescence emission (FL ~ 0.5) located in the bluish-green region. The Stokes' shift of these compounds is ca. 3779 cm-1, which was attributed to an intramolecular charge transfer (ICT) state. In CHCl3 solution, the compounds exhibited longer and shorter lifetimes, which was attributed to the emission of monomeric and aggregated molecules, respectively. Density functional theory was used to model the electronic structure of the compounds 9a-d in their excited and ground electronic states. The simulated emission spectra are consistent with the experimental results, with different solvents leading to a shift in the emission peak and the attribution of a π-π* state with the characteristics of a charge transfer excitation. The thermal properties were analyzed by thermogravimetric analysis and a high maximum degradation rate occurred at around 300 °C. Electrochemical studies were also performed in order to determine the band gaps of the molecules. The electrochemical band gaps (2.48-2.70 eV) showed strong correlations with the optical band gaps (2.64-2.67 eV).